Apakah Analisis ARDL dalam Pembiayaan Rahn Dapat Mendorong Pertumbuhan Industri Makanan dan Minuman di Indonesia? - Aisyah Hamzah; Siti Nur Azizah; Sunarsih Sunarsih; Taufikur Rohman; Agus Septian Ansori (Muttaqien, 2026)
This study aims to analyze the impact of *rahn* (Islamic pawn) financing and the exchange rate on the growth of the food and beverage (FNB) industry in Indonesia, utilizing quarterly data from 2017Q1 to 2025Q1. The rahn variable is proxied by the outstanding volume of Sharia pawn loans from Pegadaian Syariah, while the exchange rate serves as a macroeconomic control variable. The ARDL analysis reveals that rahn financing has a significant negative impact on FNB growth in both the short term (coefficient: -37.88; p = 0.0194) and the long term (coefficient: -30.79; p = 0.0045), whereas the exchange rate is statistically insignificant across both time horizons. These findings suggest that increased reliance on rahn tends to reflect a need for emergency liquidity, or "survival financing", rather than a drive for productive economic activity; consequently, there is a need to strengthen productive rahn schemes to support the development of an inclusive and sustainable halal economy.